Promoting Kindergarten Teachers' Personal and Professional Well-Being Through a Program Based on Positive Psychology - Dafna Armoza-Levi; Alina S. Rusu (Babes-Bolyai University, 2024)
This study aims to test the effect of a program intended to promote personal and professional well-being for kindergarten teachers. The program is based on positive psychology and social-emotional learning (SEL) principles. Seventy-seven kindergarten teachers from Israel participated in the study. The research tools used were four questionnaires that had to be filled out at the program's beginning and end. The results indicate that the program was able to promote the personal and professional well-being of kindergarten teachers, lower the level of stress they experience in their work, and increase the degree of job satisfaction. These findings were achieved through practical and applied tools for their daily and professional lives based on the PARMA model of positive psychology and the SEL model. The research findings have an important value in raising awareness of the issue and implementing similar programs as an integral part of the training processes of kindergarten teachers and their professional development processes.